Advance Selling in Marketing Channels - Li, Krista J.; Li, Xi (Journal of Marketing Research, 2023)
Manufacturers and retailers often advance sell seasonal products or services (e.g., holiday decorations, summer or winter entertainment). The authors examine advance selling in marketing channels to offer several insights. First, it is well established that a decentralized channel suffers from the issue of double marginalization; that is, the manufacturer and retailer both add positive margins when setting their prices, which results in inefficiently high retail prices. The authors find that, under a dynamic wholesale-price contract, advance selling can alleviate this double-marginalization problem and benefit the manufacturer, the retailer, and consumers. Second, the benefit of advance selling diminishes with the product's holding cost, the retailer's stockpiling ability, and the manufacturer's commitment to spot wholesale price. Third, with wholesale-price commitment, advance selling benefits the manufacturer and consumers but hurts the retailer; the manufacturer is better off making a price commitment only when its product's holding cost is sufficiently low and worse off otherwise. Last, the retailer's stockpiling ability decreases its own profit under a dynamic contract but increases it under a commitment contract.